2005
DOI: 10.1007/s10534-005-1247-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased cellular zinc levels on gene and protein expression in HT-29 cells

Abstract: High cellular zinc concentrations lead to impairments in ATP synthesis and cell cycle control particularly in neurons and epithelial cells. The molecular basis for these dysfunctions is still not fully elucidated. Here we analyzed the effects of a high zinc exposure (10 ppm) on gene and protein expression in the human epithelial cell line HT-29. Of the 1176 genes analyzed with cDNA arrays, nine differentially expressed genes were identified. Proteome analysis based on 1310 detected proteins identified 11 molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 49 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…Previous studies suggested that cellular targets of elevated intracellular free Zn are diverse and may include organelles such as mitochondria or lysosomes, particular enzymatic systems or individual nuclear genes (Dineley et al 2003;Kindermann et al 2005;Ostrakhovitch and Cherian 2005;Yu et al 2009). Moreover, available evidence in the literature suggests differing dynamics of this process in various models, with relative scarcity of data in solid tumor cells (Ostrakhovitch and Cherian 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that cellular targets of elevated intracellular free Zn are diverse and may include organelles such as mitochondria or lysosomes, particular enzymatic systems or individual nuclear genes (Dineley et al 2003;Kindermann et al 2005;Ostrakhovitch and Cherian 2005;Yu et al 2009). Moreover, available evidence in the literature suggests differing dynamics of this process in various models, with relative scarcity of data in solid tumor cells (Ostrakhovitch and Cherian 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Application of this Zn 2+ chelating agent has been employed to induce functional zinc deficiency and demonstrate the role of intracellular Zn 2+ in various processes such as apoptosis, oxidant stress, properties of neuronal synaptic transmission, regulation of transcription factors such as NF-kappa β, etc. [47][48][49][50][51]. The assumption seems to be that TPEN sequesters "chelatable" or "accessible" Zn 2+ , defined vaguely as free or loosely bound Zn 2+ ; but the actual impact of TPEN on Zn-proteome has not previously been measured.…”
Section: Discussionmentioning
confidence: 99%
“…For example, zinc(II) is essential for many cellular processes, including DNA synthesis, transcription, and translation, but its excess can be toxic (Babich and Stotzky 1978;Kindermann et al 2005). In order to find the optimal quantity of zinc additive, different trials should be performed using controlled minimal media instead of rich LB (Outten and O'Halloran 2001).…”
Section: Protein Expressionmentioning
confidence: 99%